Customer satisfaction towards KTM Komuter facilities and front liner attitudes / Noorafizah Kasim - Kasim, Noorafizah (Faculty of Business Management, 2006)
This study identifies the level of customer of customer satisfaction towards KTM Komuter facilities at the station and front liner attitudes. For the purposes of this study, the exploratory research was deployed. Judgmental sampling has been utilized with 100 respondents as a sample size. Both secondary and primary data are used. Through the findings in this study, it have been derived that most of the respondent feel moderate satisfaction but in term of clear and function ability of route time clock, accessibility of disable walkway, safety of disable walkway , sufficiency of fully covered platform and function ability of public phone, most of them feel unsatisfied. Besides that, for front liner attitudes, most of the respondents feel moderate satisfaction.